Malaysian Timber Industry policy: achievements, challenges and lessons learned - Ab Latib, Hazirah; Ratnasingam, Jegatheswaran; Mariapan, Manohar; Othman, Kamaruzaman; Amir, Mohd Afthar; Liat, Lim Choon; Yi, Lee Yan; Loras, Florin; Farrokhpayam, Saeid Reza; Jegatheswaran, Natkuncaran (North Carolina State University, 2022)
The National Timber Industry Plan was the first major dedicated policy framework for the wood products industry in Malaysia. This plan aimed to transform the industry into a high value-added products manufacturer and exporter, with a targeted export value of USD 13 billion in 2020. Unfortunately, this target was revised downwards in 2017 due to stagnating growth; in 2020, wood products export was valued at USD 5.43 billion. A survey of 914 different wood products manufacturers, involving sawmillers, molding, furniture, and joinery manufacturers, were conducted to examine the constraints faced, and the weaknesses of the policy framework that hampered its intended objectives. The results revealed that the policy framework did not have much impact on transforming the industry, and its growth continued to be fueled by incremental factor inputs, rather than by productivity gains. Uncertainty with the policy framework, especially with addressing raw materials supply and workforce, were highlighted as the two most important constraints faced. In essence, the outcomes suggest that business confidence, associated with industrial growth factors, are the prerequisite for the policy framework to succeed, and if confidence falters, it will adversely affect the targeted outcome of the policy.